Penerapan Teknik Active Cycle of Breathing Technique (ACBT) dalam Mengatasi Penumpukan Sekret pada Penderita Tuberculosis Paru - Yoany Maria Vianney Bita Aty; Betrice Amelia Benu; Yustinus Rindu; Trivonia Sri Nurwela (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
ACBT training as a form of handling secretion buildup in ineffective airway clearance problems experienced by Pulmonary Tuberculosis Patients. This study aims to apply the ACBT technique to remove retained secretions in patients with Pulmonary Tuberculosis in the Penfui Health Centre Working Area, Kupang City, East Nusa Tenggara. this research is a case study with a descriptive study design. The number of participants was 2 people with pulmonary tuberculosis. The results of this study are that the application of ACBT exercises in patients with pulmonary tuberculosis is very effective for removing retained secretions with ineffective airway clearance nursing problems carried out by applying ACBT exercises to patients for 3 days and there is sputum discharge on day 3. After assessing the respiratory system in 2 patients with Pulmonary TB at Penfui Health Centre, Kupang City, it can be concluded that the complaints of the two patients with Pulmonary TB have similarities where both complain of having a cough for more than 1 month, coughing white phlegm tends to be in the morning this is in line with previous research. ACBT (Active Cycle Breathing Thecnigue) exercise in patients with Pulmonary Tuberculosis, it can be concluded that the intervention of applying ACBT exercises is able to help deal with the problem of ineffective airway clearance due to retained secretions in patients with Pulmonary Tuberculosis.